PENGARUH JIWA KEWIRAUSAHAAN DAN MOTIVASI TERHADAP KEBERHASILAN USAHA TANI MASYARAKAT DESA FENEDANU KECAMATAN SOMAMBAWA - Ohahauni Telaumbanua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
This research aims to determine the influence of entrepreneurial spirit and motivation on the success of farming in the community of Fenedanu Village, Somambawa District. The type of research used in this research is quantitative research. The type of data used in this research is quantitative research and data obtained through distributing questionnaires to the community of Fanedanu Village. The population in this research is the people of Fanedanu Village who farm. The sampling technique is purposive sampling with a sample of 34 people. The data collection technique used in this research is the questionnaire technique. The data analysis technique used is multiple linear regression analysis. The results of this research show that partially and simultaneously, the variables of entrepreneurial spirit and motivation have a positive and significant effect on the success of the farming business of the Fanedanu Village community. The conclusion in this research is that the entrepreneurial spirit variable and the motivation variable have a positive and significant effect on the success of the farming business of the Fanedanu Village community. The suggestion in this research is, in order to run a business successfully, people must have an entrepreneurial spirit and motivation so that people can overcome business risks by minimizing existing risks so that the business can provide profits that are greater than the expenditure.